2018
DOI: 10.1002/path.5094
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of EZH2 in conjunctival melanoma offers a new therapeutic target

Abstract: Malignant melanoma of the conjunctiva (CM) is an uncommon but potentially deadly disorder. Many malignancies show an increased activity of the epigenetic modifier enhancer of zeste homolog 2 (EZH2). We studied whether EZH2 is expressed in CM, and whether it may be a target for therapy in this malignancy. Immunohistochemical analysis showed that EZH2 protein expression was absent in normal conjunctival melanocytes and primary acquired melanosis, while EZH2 was highly expressed in 13 (50%) of 26 primary CM and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In the eye, EZH2 protein expression can be detected in the keratinocytes of normal conjunctiva, but it has not been found in normal conjunctival melanocytes and PAM. EZH2 is highly expressed in 50% of primary conjunctival melanomas and 88% of lymph node metastases [46]. High EZH2 is correlated with CjM thickness and poor prognosis.…”
Section: Other Genetic Alterations and Chromosome Abnormalities Inmentioning
confidence: 99%
See 2 more Smart Citations
“…In the eye, EZH2 protein expression can be detected in the keratinocytes of normal conjunctiva, but it has not been found in normal conjunctival melanocytes and PAM. EZH2 is highly expressed in 50% of primary conjunctival melanomas and 88% of lymph node metastases [46]. High EZH2 is correlated with CjM thickness and poor prognosis.…”
Section: Other Genetic Alterations and Chromosome Abnormalities Inmentioning
confidence: 99%
“…Inactivation of EZH2 upregulates the oncogene p21/CDKN1A , that controls cellular transition from the G1 to S phase. Moreover, p21 levels are higher after the genetic than the pharmacological inhibition of EZH2, suggesting that EZH2 can regulate transcription using different pathways in addition to its catalytic activity [46]. Inhibition of EZH2 in CjM cells slows the cellular progression to the S-phase and determines cell death through apoptosis and autophagy.…”
Section: Other Genetic Alterations and Chromosome Abnormalities Inmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Evidence showed that EZH2 may have a dual role in cancer development, acting as a tumour suppressor or an oncogene depending on the type of cancer. [9][10][11] However, EZH2 inactivation medicated by mutation or under-expression in myelodysplastic syndromes (MDS) or myeloproliferative neoplasms (MPN) can contribute to disease pathogenesis and is associated with a poor prognosis. [9][10][11] However, EZH2 inactivation medicated by mutation or under-expression in myelodysplastic syndromes (MDS) or myeloproliferative neoplasms (MPN) can contribute to disease pathogenesis and is associated with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…8 Overexpression of EZH2 was observed in numerous solid tumours, and targeting EZH2 can cause regression of carcinogenesis. [9][10][11] However, EZH2 inactivation medicated by mutation or under-expression in myelodysplastic syndromes (MDS) or myeloproliferative neoplasms (MPN) can contribute to disease pathogenesis and is associated with a poor prognosis. [12][13][14][15] In AML, EZH2 mutation was associated with −7/del(7q) and low bone marrow blast percentage but not affected prognosis.…”
Section: Introductionmentioning
confidence: 99%